Age effects, unobserved characteristics and hedonic price indexes: The Spanish car market in the 1990s - Xosé-Luís Varela-Irimia (SERIEs - Journal of the Spanish Economic Association, 2014)
This paper computes and compares alternative quality-adjusted price indexes for new cars in Spain in the period 1990 - 2000. The proposed hedonic approach simultaneously controls for time-invariant unobserved product effects and age effects, that can be interpreted as a proxy for time-variant unobservables. The results show that the non-adjusted price index largely overstates the increase in the cost of living induced by changes in car prices and that the previous evidence for this market has not measured the real extent of that bias, probably due to the omission of controls for unobservables. It is also shown that omitting age effects can lead to misleading conclusions. In particular, their omission would imply that the year-on-year Spanish Consumer Price Index would have been overestimated by around 0.1 % on average during the sample period. Excluding both the controls for age effects and time-invariant unobservables would have increased this bias to 0.2 % . The estimated price indexes give also some insights on what could have been the determinants of price evolution in the Spanish car market.
Keywords: C43; E31; L11; L13; 330; Hedonic price indexes; Spanish car market; Car prices; IPC; CPI; Cost of living